The Effect of Social Infrastructure on Rural Poverty in Indonesia with The Village Development Index As Moderation Variable - Hanif Afif Naufal; Mulyanto Mulyanto; Suryanto Suryanto (EKO-REGIONAL, 2023)
Indonesia's poverty predominates in rural areas with minimal access to basic infrastructure. This study aims to analyze: (1) the effect of educational infrastructure on rural poverty; (2) the influence of health infrastructure on rural poverty; (3) Development Village Index (IDM) moderates the effect of the number of schools and the number of health facilities on rural poverty. Social infrastructure is measured based on educational infrastructure (number of elementary, junior high school, high school, university buildings) and health infrastructure (number of hospital buildings and community health centers), while poverty is measured by the percentage of rural poverty. The data source used is from the results of a national scale survey, namely the 2018-2021 Podes. The analytical method uses multiple linear regression models and moderation tests. The results of the analysis show that the number of schools has a negative and significant effect on rural poverty, while the number of health facilities has a positive and significant effect on rural poverty. And based on the results of the moderation test that IDM is a moderating variable that can strengthen the relationship between the number of schools and the number of health facilities to rural poverty in Indonesia.